A Tripartite Evolutionary Game Analysis of the Co-Construction of an International Transport Corridor - Yang Lei (Discrete Dynamics in Nature and Society)
The construction and development of international transport corridors have become a means of cross-border space governance and promote the flexibility of international industrial chains and supply chains. Due to the uncertainty of cooperation, the development of international transport corridors entails a long-term and complex system of engineering. This paper evaluates a tripartite evolutionary game model on the cooperative construction of international transport corridors (including origin, transit, and destination countries) and analyzes the cooperation mechanism and influencing factors. The cooperative construction of international transport corridors is complex. Factors such as willingness to cooperate, transfer payments, sunk costs, and reputation have a positive impact on the cooperative construction of international transport corridors, but excessive transfer payments hinder cooperation. To promote the construction of international transport corridors, all parties need to have a strong willingness to cooperate; otherwise, the cooperation agreement has a greater probability of becoming invalid. International transport corridors with good development prospects and benefits would accelerate construction progress with the active efforts of participating countries.